VANILLA YERSINIANA (ORCHIDACEAE), A NEW RECORD FOR PENINSULAR MALAYSIA - Muhammad Ikhwanuddin Mat Esa; Farah Alia Nordin; Rusea Go; Akmal Raffi (Reinwardtia, 2021)
MAT ESA, M. I., NORDIN, F. A., GO, R. & RAFFI, A. 2021. Vanilla yersiniana (Orchidaceae), a new record for Peninsular Malaysia. Reinwardtia 20(2): 51−55. — The genus Vanilla Plum. ex Mill. from Peninsular Malaysia is now enriched with the discovery of a newly recorded species, Vanilla yersiniana that made up its regional diversity to eight taxa. This species was documented from two adjacent secondary lowland forests in Perak; further south to the southern tail of Thailand. This paper describes the first record of V. yersiniana in Peninsular Malaysia with some highlights of its morphology and ecology. The data presented will add to the present state of knowledge on the species botanical profile.